Intestinal Barrier Interactions with Specialized CD8 T Cells - Konjar, Špela; Ferreira, Cristina; Blankenhaus, Birte; Veldhoen, Marc (Frontiers in Immunology, 2017)
The trillions of microorganisms that reside in the gastrointestinal tract, essential for nutrient absorption, are kept under control by a single cell barrier and large amounts of immune cells. Intestinal epithelial cells (IECs) are critical in establishing an environment supporting microbial colonisation and immunological tolerance. A large population of CD8+ T cells is in direct and constant contact with the IECs, the intraepithelial lymphocytes (IELs). Due to their location, at the interphase of the intestinal lumen and external environment and the host tissues, they seem ideally positioned to balance immune tolerance and protection to preserve the fragile intestinal barrier from invasion as well as immunopathology. IELs are a heterogeneous population, with a large innate-like contribution of unknown specificity, intercalated with antigen-specific tissue resident memory T cells. In this review, we provide a comprehensive overview of IEL physiology and how they interact with the IECs and contribute to immune surveillance to preserve intestinal homeostasis and host – microbial relationships.